PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH DIVARIASI DENGAN PENERAPAN ICE BREAKER UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 3 TALIABU UTARA - Abdul Rasid Saraha; St. Hayatun Nur Abu; Hayatun Nufus (Universitas Khairun, 2022)
This study aims to determine the effect of the variation problem based learning model with the implementation of Ice Breaker towards student’s learning outcomes of class 11 IPA at SMA Negeri 3 Taliabu Utara about chemical equilibrium. The type of research used in this study is experimental research with a one group pretest posttest design. The samples of this study were 20 students of class 11 IPA at SMA Negeri 3 North Taliabu which were selected by using saturated sampling technique. The instruments used in this Study were in the form of essay questions consisting of 8 items to measure students’ learning outcomes and observation sheet to measure of the effective and psychomotor domains. The data analysis technique used in this study was inferential statistical analysis using SPSS 21.0. The results of analysis showed that there effect of variation problem based learning model with the implementation of Ice Breaker towards students’ learning outcomes of class 11 IPA at SMA Negeri 3 North Taliabu about chemical equilibrium, with the results of hypothesis test obtained:tcount<ttable or -8.205<1.729, meanwhile the results of affective domain anlysis reached 53 and psychomotor domain reached 53.